Analisis Cemaran Logam Berat (Pb, Cd, Zn) pada Ikan Tuna Kemasan Kaleng dengan Metode Spektrofotometri Serapan Atom (SSA) - Tiwi Setianingrum; Adita Silvia Fitriana; Dessy Nawangsari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Fish is one type of aquatic product widely used by the community because of its advantages as a food ingredient, including a source of important nutrients such as protein, vitamins, fat, and minerals. Fish is often found in cans. Canned packaging contains the heavy metals lead (Pb), cadmium (Cd), and zinc (Zn), which can be released into food due to the long storage period. This study aims to identify and analyze heavy metals Pb, Cd, and Zn levels in canned tuna with an expiration date of less than 1 year. Samples of canned tuna came from five different brands. Qualitative analysis used color reagents, while quantitative research used an atomic absorption spectrophotometer (AAS). The qualitative study results showed that three samples of tuna contained heavy metals. Samples B and C were positive for Pb metal, while samples A and B were positive for Zn metal. The concentration of Pb metal was measured in sample B at 117.9 mg/Kg and in sample C at -0.0147 mg/Kg. The concentration of Zn metal in sample A was -0.0048 mg/Kg, and in sample B, it was -0.147 mg/Kg.